Pembungaan Kembali Tanaman Mawar (Rosa SP.) Sebagai Tanaman Taman Melalui Pemangkasan dan Pemberian Pupuk - Dini Qowiyah Ula; Nur Azizah; Agus Suryanto (PLANTROPICA: Journal of Agricultural Science, 2019)
Roses is one of popular and widely cultivated commodities in Indonesia. Based on usefulness, roses can be classified into cut flowers, potted flowers and garden elements. Roses used as garden ornamental plants because it is able to improve aesthetics of garden and create comfortable atmosphere for visitors garden. The purposes of the research was to study the effect and obtain the level of pruning and appropriate concentration of foliar fertilizer for growth and flowering of roses. The hypothesis of the research were to get  influence and get right level of pruning and foliar fertilizer concentration that can increase growth and flowering of roses. The research was conducted in March to June 2018 at Venus Orchid and Nursery, Malang. Split Plot Design with 3 repetition, foliar fertilizer as main plot and prunning as sub plot. Parameters observed included growth and flowering roses. Growth variables include number of shoots (shoots), length of branches (cm), time of budding (hsp), number of leaves (strands), and leaf area (cm2). Flowering variables include the number of flowers (flower per plant), the length of the stalk flower (cm), the diameter of the flower (cm), time of flowering (hsp), time of blooming (hsp), and vase life (day). The results showed that 1500 ppm concentration of foliar fertilizer with hard pinch 1 pruning was able to increase 34.47% of the branch length, accelerate the emergence of branch buds 70 days, increase 3.66 flowers and accelerate 14.16 days when flowering on roses compared to treatments without pruning and foliar fertilizer